2018
DOI: 10.18632/oncotarget.24794
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism ofSLC31A1is associated with clinical outcomes of platinum-based chemotherapy in non-small-cell lung cancer patients through modulating microRNA-mediated regulation

Abstract: SLC31A1 is the major transporter for platinum drug intake, its expression correlates with drug disposition and response. In 1004 Chinese NSCLC patients with platinum-based chemotherapy, we investigated the association between SLC31A1 polymorphisms and clinical outcomes. Heterozygotes of rs10759637 at 3′UTR was associated with severe thrombocytopenia (odds ratio [OR]: 2.69; P = 0.012) and shorter overall survival (hazard ratio [HR]: 1.24; P = 0.005). Variant homozygote of rs2233914 was correlated with longer ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The main characteristics for the 1004 eligible patients of the two panel cohorts in total and their clinical outcomes including objective response, toxicity and survival are summarized in Table 1 were documented in detail in our recent report 9 . Briefly, 177 (18.1%) of the 975 patients evaluated were responders (one was complete response, CR, and 176 were partial response, PR), and 798 (81.9%) were non-responders (610 showed stable disease, SD, and 188 showed progressive disease, PD).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The main characteristics for the 1004 eligible patients of the two panel cohorts in total and their clinical outcomes including objective response, toxicity and survival are summarized in Table 1 were documented in detail in our recent report 9 . Briefly, 177 (18.1%) of the 975 patients evaluated were responders (one was complete response, CR, and 176 were partial response, PR), and 798 (81.9%) were non-responders (610 showed stable disease, SD, and 188 showed progressive disease, PD).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that SLC31A1 polymorphisms overall were not associated with response 9 , except rs2233914 (G/A), a common variant at 5' flanking region upstream the transcription start site that was associated with poor response in dominant model (OR 0.67; 95% CI 0.48-0.95; P = 0.024) ( Supplemental Table 4 ). In an effort to interrogate pharmacogenetically relevant genetic interaction between platinum drug intake and export pathways, we investigated the joint effect of ABCG2 (rs1871744 and rs2231142) and SLC31A1 (rs2233914) genotypes on response in the total cohort (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since we did not observe changes in the expression of the validated miR-29 targets AKT3, MCL1, and DNMT3B, we identified new targets that might constitute vulnerabilities of melanoma. Of the 9 genes identified by our approach (KCTD5, MYBL2, SLC31A1, MAFG, RCC2, TUBB2A, SH3BP5L, SMS and NCKAP5L), RCC2, MYBL2 and SLC31A1 have previously been identified as miR-29 targets (Martinez et al 2011;Matsuo et al 2013;Wu et al 2013;Hu et al 2014;Sun et al 2018). We selected MAFG for further analyses because the protein is stabilized by ERK-mediated phosphorylation (Fang et al 2016), suggesting that MAPK signaling converges on MAFG via ERK and miR-29.…”
mentioning
confidence: 99%